2017
DOI: 10.1111/joic.12381
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the nephrotoxic effects of iodixanol versus iohexol in patients with chronic heart failure undergoing coronary angiography or angioplasty

Abstract: In patients with chronic heart failure with reduced ejection fraction who are currently undergoing coronary angiography with or without percutaneous coronary intervention, the iso-osmolar contrast iodixanol was associated with a lower incidence of contrast induced nephropathy than low-osmolar contrast iohexol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…However, most study reports evaluating the incidence of CI-AKI focused on low-osmolar contrast agents [11,33]. Recent data support the use of iso-osmolar contrast media to prevent CI-AKI both for intravenous and intraarterial administration, particularly in the setting of CKD [34][35][36][37]. In a randomized clinical trial performed in cancer patients, Terrenato et al reported a more favorable safety profile of Iodixanol vs. Iopromide [37].…”
Section: Discussionmentioning
confidence: 99%
“…However, most study reports evaluating the incidence of CI-AKI focused on low-osmolar contrast agents [11,33]. Recent data support the use of iso-osmolar contrast media to prevent CI-AKI both for intravenous and intraarterial administration, particularly in the setting of CKD [34][35][36][37]. In a randomized clinical trial performed in cancer patients, Terrenato et al reported a more favorable safety profile of Iodixanol vs. Iopromide [37].…”
Section: Discussionmentioning
confidence: 99%
“…Nie et al (2008) compared the incidence of CI-AKI in patients with CKD, who underwent coronarography with or without percutaneous revascularization, randomized to iodixanol vs iopromide, experiencing an incidence of CI-AKI significantly lower in the IOCM group compared with the LOCM patients (5.7 vs 16.7%; P = 0.011). Song et al (2017) randomized 220 patients with heart failure and reduced left ventricular systolic function (with or without PCI) to iodixanol or iohexol. The primary endpoint was the incidence of CI-AKI 72h after the coronary procedure.…”
Section: Contrast Media Osmolality To Reduce the Risk Of Contrast-indmentioning
confidence: 99%
“…The side effects induced by ICAs are partially attributed to their hypertonic or hypotonic properties. Although the third generation ICAs, namely nonionic dimer such as iodixanol, possesses iso-osmolality and are believed to induce lower incidence of side effects [6], they still may lead to nephropathy and adverse cardiac events [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%